A Very Early “Fashion”: Neolithic Stone Bracelets from a Mediterranean Perspective - Martínez-Sevilla Francisco (De Gruyter, 2021)
Ring-shaped objects, used mainly as bracelets, appear in the archaeological record associated with the first farming societies around the Mediterranean area. These bracelets, among other personal ornaments, are related to the spread of the farming economy in the Mediterranean (10th–6th millennium BC). In particular, stone bracelets, given their intricate technology, are linked with the early stages of craft specialization and the beginnings of complex social organization. Likewise, their frequency in Early Neolithic assemblages and the lithologies in which they were made have become an important element in the study of the circulation networks of goods, as well as the symbolic behaviors and aesthetic preferences of the first farming groups. This research provides the first overview of the stone bracelets of Neolithic groups in the Mediterranean. We compare the similarities and differences among these ornaments in different geographical zones across the region including Turkey, Greece, Italy, and Spain. Using all the information available about these ornaments – chronology, typology, raw materials and manufacturing processes, use-wear, repair, and alteration practices – we shed light on a complex archaeological trans-cultural manifestation related to the spread of the Neolithic lifestyle across the European continent.